2020
DOI: 10.1016/j.wem.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hamstring Muscle Tears in Climbers—Current Rehabilitation Concepts

Abstract: Acute hamstring injuries are often caused by the heel hook technique. This technique is unique to climbing and causes injury to muscular and inert tissues of the posterior thigh. The heel hook is used by climbers during strenuous ascent on overhanging walls and when crossing difficult terrain. The technique reduces the amount of upper body strength required during strenuous climbing because the climber's center of mass is retained within the base of support. The heel hook is stressful collectively for the hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
(159 reference statements)
0
4
0
Order By: Relevance
“…Lutter et al demonstrated that climbers may suffer knee joint injuries while employing the heel hook technique (HH) [31]. Some of these injuries involve muscles of the hamstring group, especially the biceps femoris muscle, and the iliotibial band, which is attached to the gluteus maximus muscle [32,33]. So, another result of the above research is the knowledge of which muscle groups are overloaded during prolonged practice of the sport.…”
Section: Discussionmentioning
confidence: 99%
“…Lutter et al demonstrated that climbers may suffer knee joint injuries while employing the heel hook technique (HH) [31]. Some of these injuries involve muscles of the hamstring group, especially the biceps femoris muscle, and the iliotibial band, which is attached to the gluteus maximus muscle [32,33]. So, another result of the above research is the knowledge of which muscle groups are overloaded during prolonged practice of the sport.…”
Section: Discussionmentioning
confidence: 99%
“…Performance on all of these measures was strongly enhanced relative to the first assessment. These findings are important, particularly given the lack of climbing related rehabilitation programs 4 5 11 12 as well as the rise in incidence of shoulder injuries in climbers 10 16 20 .…”
Section: Discussionmentioning
confidence: 99%
“…As climbing becomes more popular, it is essential for medical professionals and physical therapists to better understand and treat climbing-related injuries [6]. Little work was done onto prevention and rehabilitation after overstrain injuries yet [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Off the wall climbing specific neuromuscular performance is initiated when pain and strength loss is negligible compared with the contralateral side. It is important to continue to monitor the response to mechanical load during each progression and after training (55). Climbing specific neuromuscular performance is important to restore maximal force expression (56), rate of force development, energy storage (57), and the local muscular endurance (58) of the finger muscle, tendons, and the shoulder girdle muscles.…”
Section: Periodizationmentioning
confidence: 99%